Cavernous transformation of portal vein a missed cause of extrahepatic portal hypertension - Vaish, Arvind Kumar (BMJ Publishing Group, 2012)
The portal vein thrombosis is an important and well-known cause of portal hypertension in young patients. Cavernous transformation of portal vein may be a sequel of portal vein thrombosis. Here the author reports a case of a 14-year-old boy presented with haemetemesis and melena, which was due to rupture of oesophageal varices as a result of portal hypertension. On further investigation, cavernous transformation of portal vein was identified on CT portovenogram and normal liver structure was evident on histology.